The role of strategic position in brand promise: Evidence from LG Company - A. Eilaghi Karvandi (Management Science Letters, 2016)
This paper presents an empirical investigation to study the effects of different strategies including attribute, advantage, application, consumer, competitive advantage, pricing/quality and category on brand promise for products of LG Company in city of Tehran, Iran. The study designs two questionnaires, one for strategic positioning and the other for brand promise in Likert scale. Cronbach alphas for brand promise and strategic positioning are 0.81 and 0.79, respectively. The questionnaires are distributed among 385 randomly selected regular users of LG products and using Spearman correlation as well as Stepwise regression techniques, the effects of various strategies on brand promise are examined. The results of the implementation of Spearman correlation have indicated that there were positive and meaningful relationships between different strategies and brand promise. In addition, the results of Stepwise regression have indicated that three strategies of price/quality, consumer and application were the most important predictors of brand promise.